A method for manufacturing an electric heating anti-freezing rain and sand separator vane and the separator vane
Patent Information
- Application Number
- CN202611138225.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]为此,本发明所要解决的技术问题在于克服现有技术中现有雨沙分离器叶片普遍存在防冻除冰效果差、通风效率与防护性能无法兼顾、加热结构易失效、涂层稳定性不足等缺陷,提供一种电热防冻雨沙分离器叶片制造方法及分离器叶片
[0019]The present invention discloses a method for manufacturing electrothermal antifreeze rain and sand separator blades and separator blades. First, an anodized film with a nanoporous honeycomb structure is constructed on the surface of an aluminum alloy substrate. Then, a conductive primer is allowed to penetrate into the pores of the oxide film. The bonding strength between the conductive primer layer and the substrate interface is significantly improved by relying on the nanomechanical anchoring effect. Then, a graphene coating is coated on the conductive primer layer and a conductive heating layer is formed by gradient curing. This ensures that the graphene conductive heating layer is uniformly formed and reduces internal defects in the coating. The finished blade can then be obtained by connecting it with a metal electrode.
Smart Images

Figure CN122913064A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-icing technology for ventilation equipment, and in particular to a method for manufacturing blades of an electrothermal antifreeze rain and sand separator and the separator blades themselves. Background Technology
[0002] In high-altitude and cold regions where sandstorms, rain, and snow are frequent, the sand and rain separation louvers of the ventilation system are the core components for ensuring indoor air quality and stable operation of the ventilation system. They not only need to effectively block sandstorms, rain, and snow, but also need to continuously maintain a stable ventilation state and withstand the test of extreme low temperature weather.
[0003] Currently, most conventional ventilation louvers on the market are designed to block rainwater, offering poor filtration and protection against strong winds, sandstorms, and heavy rain. While some electrically adjustable louvers can improve protection by reducing or closing the slats, this directly reduces the ventilation system's airflow, failing to balance protection and ventilation efficiency. Particularly concerning is that in extreme low temperatures and snow, snow and ice easily accumulate on the louver surfaces, causing airflow blockage, louver failure, and ventilation system shutdown, severely impacting normal equipment operation.
[0004] Existing technologies include anti-icing louver structures, such as heating and melting ice by installing electric heating tape on the louver structure. The heated louver structure melts rain, snow, and ice layers and, in conjunction with the structure, allows for the automatic discharge of sand and snow. However, this traditional electric heating structure has significant technical defects. External electric heating tape occupies ventilation duct space, disrupts airflow, and significantly reduces the overall ventilation efficiency of the equipment. Furthermore, the installation process of wrapping and attaching the electric heating tape is complex, greatly increasing the product manufacturing and assembly costs. At the same time, the electric heating tape cannot achieve full coverage heating of the blade surface, resulting in heating blind spots, uneven blade heating, inconsistent de-icing and antifreeze effects, and poor reliability in actual use.
[0005] Currently, the mainstream solutions for icing on louver blades in the industry are mainly divided into two categories: passive anti-icing and active de-icing. Passive anti-icing solutions mostly use spraying with fluorinated hydrophobic anti-icing coatings to reduce the adhesion of ice by lowering the surface energy of the blades. However, this solution can only slightly slow down the icing rate. Under harsh conditions of continuous low temperature and high humidity, the anti-icing effect is greatly reduced, and it cannot achieve active melting and de-icing, making it unsuitable for extreme usage scenarios in cold regions. Active de-icing solutions mainly use electric heating technology. By energizing electric heating elements inside or on the surface of the blades, active de-icing and antifreeze are achieved, which is also the most effective technology for antifreeze at present.
[0006] Currently, the mainstream active electric heating structures include heating wires and traditional electric heating films. Among them, the heating wire structure has problems such as poor heating uniformity and mismatch between the thermal expansion coefficients of the heating wire and the aluminum alloy blade substrate. It is prone to fatigue fracture failure under long-term alternating hot and cold conditions. In addition, the external wire structure will disrupt the aerodynamic structure of the blade and the airflow path for rain and sand separation, reducing the rain and sand separation effect and ventilation efficiency. Traditional electric heating film technology is always limited by the interface bonding strength between the substrate and the conductive coating. The coating is prone to peeling and flaking, resulting in short service life and poor weather resistance. Graphene, with its excellent electrical and thermal conductivity, chemical stability, and mechanical properties, has become the preferred material in the field of electrothermal coatings and is widely used in the research and development of various electric heating devices. However, the existing technology has not yet formed a complete supporting system for graphene electrothermal coatings, and it is impossible to construct a multi-layer composite graphene electrothermal coating structure on the surface of aluminum alloy blade substrates that has strong interfacial adhesion, high wear resistance, excellent corrosion and weather resistance, and electrical safety. Problems such as poor coating bonding, poor heating stability, insufficient insulation, and easy leakage failure are common. In addition, there is a lack of standardized preparation process adapted to the working conditions of rain and sand separator blades, making it difficult to realize industrial application. Summary of the Invention
[0007] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing rain and sand separator blades, such as poor antifreeze and de-icing effect, inability to balance ventilation efficiency and protection performance, easy failure of heating structure, and insufficient coating stability, and to provide a method for manufacturing electric heating antifreeze rain and sand separator blades and separator blades.
[0008] To solve the above-mentioned technical problems, the present invention provides a method for manufacturing an electrothermal antifreeze rain and sand separator blade, comprising: step S1, using a pre-treated aluminum alloy substrate as an anode for anodizing treatment until an anodized film with a nanoporous honeycomb structure is formed on the surface of the aluminum alloy substrate; step S2, coating the surface of the anodized film with a conductive primer until the conductive primer penetrates into the nanoporous honeycomb structure of the anodized film, and obtaining a conductive primer layer after drying and curing; step S3, coating the surface of the conductive primer layer with at least one layer of graphene coating, and obtaining at least one conductive heating layer after gradient curing; step S4, leading out a metal electrode from the conductive heating layer to obtain the target electrothermal antifreeze rain and sand separator blade.
[0009] In one embodiment of the present invention, step S1 specifically includes: step S11, performing pretreatment processing on the aluminum alloy substrate, wherein the pretreatment processing includes alkaline degreasing, water washing, and acid pickling activation treatment sequentially performed on the surface of the aluminum alloy substrate; step S12, placing the pretreated aluminum alloy substrate in a sulfuric acid electrolyte for anodizing treatment, controlling the current density to be 1.0~1.2A / dm³. 2The electrolyte temperature is 18~22℃, the oxidation time is 8~15min, until an anodized film with a thickness of 3~5μm is formed on the surface of the aluminum alloy substrate; step S13, the anodized film is washed with water and dried to obtain an anodized film with a nanoporous honeycomb structure.
[0010] In one embodiment of the present invention, in step S12, the concentration of the sulfuric acid electrolyte is 160~180g / L, and the voltage of the anodization is initially 8V and gradually increases to 12~15V as the film thickness increases; in step S13, after anodization, the film is washed with deionized water with a conductivity ≤50μS / cm, dried to obtain an anodized film with a nanoporous honeycomb structure, and then proceeds to step S2 within 4 hours.
[0011] In one embodiment of the present invention, before performing step S2, the anodic oxide film with nanoporous honeycomb structure needs to be pretreated with silane. The silane pretreatment process includes: immersing the aluminum alloy substrate with the anodic oxide film in an ethanol / water solution with a mass concentration of 2% γ-aminopropyltriethoxysilane, soaking it at 60°C for 10 minutes, draining it, and then drying it with hot air at 80°C.
[0012] In one embodiment of the present invention, step S2 specifically includes: step S21, immersing the aluminum alloy substrate with the anodic oxide film in a low-viscosity conductive primer for 1-3 minutes, so that the conductive primer penetrates into the nanoporous honeycomb structure of the anodic oxide film, wherein the application viscosity of the conductive primer is 8-12s; step S22, curing the conductive primer to obtain the target conductive primer layer.
[0013] In one embodiment of the present invention, step S3 specifically includes: step S31, coating a graphene coating within 25-35 minutes after the conductive primer layer has dried and cured; step S32, after coating the graphene coating, drying it sequentially at 60°C for 5 minutes, at 80°C for 10 minutes, and at 120°C for 15 minutes to obtain a conductive heating layer after gradient curing; step S33, repeating step S32 until the target number of conductive heating layers is obtained; wherein, the coating method of the graphene coating is slot coating or precision roller coating; the preparation method of the graphene coating includes: dissolving a dispersant in deionized water, adding graphene powder and then sequentially dispersing it by high-speed dispersion and planetary ball milling, then sequentially adding a nano-silver wire dispersion, an aqueous polyurethane emulsion, and a crosslinking agent, and filtering after vacuum degassing to obtain a target graphene coating with a construction solids content of 25-30%.
[0014] In one embodiment of the present invention, before step S4, a protective topcoat is sprayed onto the electrode area of the conductive heating layer to mask it. After high-temperature baking and curing, the cured protective topcoat is removed to expose the electrode area of the conductive heating layer. After applying silver conductive adhesive to the electrode area, metal electrodes are pasted and installed. After hot pressing and curing, the target electrothermal antifreeze rain and sand separator blade is obtained.
[0015] The present invention also provides an electrothermal antifreeze rain and sand separator blade, which is processed by the above-mentioned electrothermal antifreeze rain and sand separator blade manufacturing method, comprising: an aluminum alloy substrate; an anodized film, wherein the anodized film covers the surface of the aluminum alloy substrate and has a nanoporous honeycomb structure arranged thereon; at least one conductive primer layer, wherein the conductive primer layer covers the surface of the anodized film and at least part of the conductive primer layer penetrates into the channels of the nanoporous honeycomb structure to form a nanomechanical anchoring structure; and a conductive heating layer, wherein the conductive heating layer covers the surface of the conductive primer layer and has a metal electrode at its end that can be connected to an external power source.
[0016] In one embodiment of the present invention, the thickness of the anodic oxide film is 3~5μm; the conductive primer layer comprises a sheet resistance ≤10. 4 The conductive carbon black and graphene microsheets have a sheet resistance of Ω / sq and a dry film thickness of 10~20μm, and the conductive primer layer penetrates to a depth of ≥1.5μm in the nanoporous honeycomb structure channels; the graphene conductive heating layer has 1~5 layers, each of which includes graphene and a binder matrix, has a sheet resistance of 30~150Ω / sq, and a dry film thickness of 30~60μm, wherein the graphene is reduced graphene oxide or liquid-phase exfoliated graphene, has a sheet diameter of 5~20μm, and a carbon-to-oxygen ratio ≥8, and the binder matrix is an aqueous polyurethane dispersion; the graphene conductive heating layer also includes silver nanowires.
[0017] In one embodiment of the present invention, the blades of the electrothermal antifreeze rain and sand separator further include a silane coupling agent layer disposed between the anodic oxide film and the conductive primer layer; the blades of the electrothermal antifreeze rain and sand separator further include a protective topcoat layer connected to the surface of the conductive heating layer, the protective topcoat layer having a dry film thickness of 30~50μm, at least a portion of the conductive heating layer being exposed outside the protective topcoat layer, the protective topcoat layer comprising nano-silica and polytetrafluoroethylene micropowder; the metal electrode comprises a silver conductive adhesive layer and a copper busbar, the copper busbar being electrically connected to the exposed conductive heating layer through the silver conductive adhesive layer.
[0018] The technical solution of the present invention has the following advantages compared with the prior art:
[0019] The present invention discloses a method for manufacturing electrothermal antifreeze rain and sand separator blades and separator blades. First, an anodized film with a nanoporous honeycomb structure is constructed on the surface of an aluminum alloy substrate. Then, a conductive primer is allowed to penetrate into the pores of the oxide film. The bonding strength between the conductive primer layer and the substrate interface is significantly improved by relying on the nanomechanical anchoring effect. Then, a graphene coating is coated on the conductive primer layer and a conductive heating layer is formed by gradient curing. This ensures that the graphene conductive heating layer is uniformly formed and reduces internal defects in the coating. The finished blade can then be obtained by connecting it with a metal electrode.
[0020] The entire preparation process is simple and controllable, facilitating industrial implementation. The blades produced by this method integrate electrothermal functions into the blade body, eliminating the need for additional external heating components such as electric heating cables and heating wires. This process does not alter the original shape and structure of the blades, nor does it interfere with the internal airflow field of the rain-sand separator. While achieving active electrothermal de-icing and preventing blade icing from blocking the air duct, it also ensures the ventilation and rain-sand separation performance of the equipment. The anodic oxide film also acts as an insulating barrier between the substrate and the conductive primer layer, reducing the risk of leakage. The gradient curing process helps improve the sheet resistance uniformity of the graphene coating, making the overall heating of the blades more uniform and reducing local overheating and heating dead zones. The resulting composite coating system has excellent adhesion and can withstand repeated thermal cycles, salt spray erosion, and wind and sand abrasion. Under long-term outdoor conditions, it is not prone to failure phenomena such as peeling, flaking, or excessive resistance drift, effectively extending the service life of the electrothermal antifreeze rain-sand separator blades. Attached Figure Description
[0021] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings.
[0022] Figure 1 This is a flowchart of the manufacturing method of the electrothermal antifreeze rain-sand separator blades in a preferred embodiment of the present invention;
[0023] Figure 2 This is a cross-sectional layer structure diagram of the blades of the electrothermal antifreeze rain-sand separator in another embodiment of the present invention;
[0024] Explanation of reference numerals in the accompanying drawings: 100, aluminum alloy substrate; 200, anodized film; 300, conductive primer layer; 400, conductive heating layer; 500, protective topcoat layer. Detailed Implementation
[0025] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0026] Example 1: Refer to Figure 1As shown, the present invention provides a method for manufacturing blades of an electrothermal antifreeze rain-sand separator, which includes:
[0027] Step S1: The pretreated aluminum alloy substrate is used as an anode for anodizing treatment until an anodized film with a nanoporous honeycomb structure is formed on the surface of the aluminum alloy substrate. This step generates an anodized film with a nanoporous honeycomb structure on the surface of the aluminum alloy substrate. On the one hand, the anodized film itself has high insulation performance and can build an insulating barrier layer between the aluminum alloy substrate and the subsequent conductive coating to avoid the safety risk of leakage of the substrate when the power is on. On the other hand, the formed open nanoporous honeycomb structure provides a physical anchoring substrate for the conductive primer, and provides a structural basis for the subsequent conductive primer to achieve in-pore penetration and build nanomechanical anchoring sites. At the same time, the oxide film can also improve the surface condition of the substrate and improve the substrate conditions for coating adhesion.
[0028] Furthermore, step S1 in this embodiment specifically includes:
[0029] Step S11: Perform pretreatment on the aluminum alloy substrate. The pretreatment includes alkaline degreasing, water washing, and acid pickling activation treatment sequentially on the surface of the aluminum alloy substrate. During this process, alkaline degreasing, water washing, and acid pickling activation treatment are carried out sequentially. Alkaline degreasing is used to remove cutting oil, processing aids, and various organic contaminants from the surface of the aluminum alloy substrate, avoiding interference from oil contaminants with oxide film growth and preventing problems such as loose oxide film and local film defects. Water washing is used to thoroughly rinse away residual degreasing agents on the workpiece surface, preventing alkaline solutions from being carried into the subsequent acid pickling process and causing local over-corrosion. Acid pickling activation can remove the naturally formed loose primary oxide layer and surface dust impurities on the aluminum alloy surface, exposing a clean and uniformly active aluminum alloy substrate surface, ensuring that the oxide film can be uniformly formed during the subsequent anodizing process, laying the foundation for obtaining a complete, continuous, and uniformly porous nanoporous honeycomb anodized film.
[0030] Specifically, in this embodiment, the aluminum alloy substrate is immersed in a weakly alkaline degreasing agent specifically for aluminum alloys, soaked at 55°C for 4 minutes with circulation and stirring. After removal, it is inspected using the water film method; a continuous water film without breaks indicates that the alkaline degreasing is qualified. Then, it sequentially passes through a recovery water washing tank, an intermediate water washing tank, and a pure water washing tank, each soaking for 1.5 minutes with compressed air stirring to complete the water washing process. Next, the workpiece is immersed in a mixed pickling solution of 12% (v / v) nitric acid and 0.8% (v / v) hydrofluoric acid at room temperature for 45 seconds to remove the natural oxide layer and form micro-roughness. Finally, it passes through an intermediate water wash and a deionized water wash, each soaking for 1 minute to complete the pretreatment process.
[0031] Step S12: The pretreated aluminum alloy substrate is placed in a sulfuric acid electrolyte for anodizing treatment, with the current density controlled at 1.0~1.2 A / dm³. 2The electrolyte temperature is 18~22℃, and the oxidation time is 8~15min, until an anodic oxide film with a thickness of 3~5μm is formed on the surface of the aluminum alloy substrate; by limiting 1.0~1.2A / dm 2 By precisely controlling the current density, electrolyte temperature (18-22℃), and oxidation time (8-15min), the growth rate and dissolution rate of the oxide film are controlled, a thin anodic oxide film with a thickness of 3-5μm can be generated on the surface of an aluminum alloy substrate. This parameter range can ensure that the oxide film forms a complete nanoporous honeycomb structure, obtaining open channels for conductive primer to penetrate, while avoiding the defects of increased internal stress, increased brittleness, and easy cracking caused by excessive film thickness. It can also prevent insufficient film thickness from causing the insulation performance to fail to meet the application requirements. The resulting oxide film simultaneously meets the dual functions of insulation and nano-anchoring of the substrate. Parameter matching ensures that the pore structure of the oxide film is uniform and controllable.
[0032] Specifically, in step S12, the concentration of the sulfuric acid electrolyte is 160~180g / L, and the voltage of the anodic oxidation starts at 8V and gradually increases to 12~15V as the film thickness increases. This coordinates the electrochemical generation rate of the oxide film with the chemical dissolution rate of the oxide film by the electrolyte, which is conducive to the formation of a nanoporous honeycomb structure with regular channels and suitable pore size. It can avoid the slow oxidation film formation rate and insufficient pore development caused by too low electrolyte concentration, and also prevent the loose and powdery film caused by excessive dissolution of the pore walls caused by too high electrolyte concentration. The voltage gradually increases with the film thickness, which can match the impedance change caused by the continuous thickening of the barrier layer, maintain the stability of the oxidation process, ensure the uniform overall thickness of the 3~5μm thin anodic oxide film, reduce local film thickness deviation, and ensure that the oxide film has qualified insulation performance and open channels that allow conductive primer to penetrate. This provides a stable and reliable film foundation for the subsequent construction of nanomechanical anchoring structures.
[0033] In this embodiment, the sulfuric acid electrolyte concentration was 170 g / L, the electrolyte temperature was 20 ± 0.5 °C, and the current density was 1.1 A / dm³. 2 The oxidation time was 12 minutes. During the oxidation process, the electrolyte was stirred with compressed air to maintain uniformity and dissipate heat. The voltage initially reached approximately 8V, gradually increasing to approximately 14V as the film thickness increased. After oxidation, the workpiece surface was a uniform light gray. It was then sequentially washed with recycled water and deionized water, each soaking for 1.5 minutes. Subsequently, surface water was blown away with compressed air, and the workpiece was dried in a 60℃ oven for 5 minutes. Eddy current thickness gauge measurements showed the oxide film thickness to be approximately 4μm, meeting the requirement of 3~5μm. Throughout this process, the nanopores remained open.
[0034] Step S13: The anodic oxide film is washed with water and dried to obtain an anodic oxide film with a nanoporous honeycomb structure. The water washing is used to rinse away the residual sulfuric acid electrolyte adhering to the surface of the workpiece, so as to avoid the electrolyte from continuously corroding and damaging the pore walls of the oxide film and to prevent the pore morphology from being eroded and changed. The drying process removes the moisture on the surface of the workpiece without sealing the oxide film, and completely preserves the inherent open nanoporous honeycomb structure of the anodic oxide film, ensuring that the pores remain transparent and that the conductive primer can smoothly penetrate into the pores to form nanomechanical anchoring sites in subsequent steps.
[0035] Specifically, in step S13, after anodizing, deionized water with a conductivity ≤50μS / cm is used for rinsing. This effectively removes residual sulfuric acid electrolyte and soluble salt impurities from the workpiece surface and inside the nanopores, preventing the residual electrolyte from continuously eroding the oxide film pore walls and preventing impurities from precipitating and accumulating, causing blockage of the nanopores. After drying, an anodized film with a nanoporous honeycomb structure is obtained and proceeds to step S2 within 4 hours. This is to strictly control the aging time of the unsealed anodized film in the air, shorten the time for the oxide film to spontaneously hydrate in contact with air and water vapor, avoid the formation of hydrated alumina on the inner wall of the pores, which would cause partial blockage of the pore openings, and maximize the permeability and openness of the nanoporous honeycomb structure pores. This ensures that the subsequent conductive primer can smoothly penetrate into the pores to form sufficient and effective nanomechanical anchoring sites, ensuring the interfacial bonding performance of the coating.
[0036] In this embodiment, before step S2, the anodic oxide film with a nanoporous honeycomb structure needs to undergo silane pretreatment. The silane pretreatment process includes: immersing the aluminum alloy substrate with the anodic oxide film in an ethanol / water solution with a mass concentration of 2% γ-aminopropyltriethoxysilane, soaking it at 60°C for 10 minutes, draining it, and then drying it with hot air at 80°C. This allows silane molecules to fully diffuse into the nanoporous honeycomb channels of the anodic oxide film. The silanol groups generated after silane hydrolysis can react with the hydroxyl groups on the surface of the oxide film pores to form Al-O. -Si covalent bonds construct a self-assembled monolayer on the pore walls, which on the one hand improves the interfacial compatibility between the inorganic oxide film and the organic conductive primer and improves the wetting effect; on the other hand, chemical bonding is introduced at the interface through chemical bonding, which works synergistically with the nanomechanical anchoring formed by the subsequent penetration of conductive primer to further improve the interfacial bonding strength and inhibit the generation of interfacial defects. Hot air drying conditions can promote the full progress of silane condensation reaction, while avoiding the formation of excess deposits in the pores by silane solution residue, which can cause pore blockage. This provides favorable conditions for the uniform wetting and firm adhesion of the subsequent conductive primer.
[0037] Step S2: Coat the surface of the anodic oxide film with a conductive primer until the conductive primer penetrates into the nanoporous honeycomb structure of the anodic oxide film. After drying and curing, a conductive primer layer is obtained. This step allows the conductive primer to fully penetrate into the nanoporous honeycomb structure of the anodic oxide film. After the primer cures, a large number of mechanical anchoring nodes are formed in the channels, which significantly strengthens the interfacial bonding force between the conductive primer layer and the anodic oxide film and inhibits the coating from delamination and peeling under alternating hot and cold conditions and wind and sand abrasion. The conductive primer also serves as a transitional intermediate layer, which can bridge the difference in physicochemical properties between the anodic oxide film and the subsequent graphene conductive heating layer, alleviate the problem of thermal stress mismatch between the two layers, and provide a good coating substrate for graphene coatings.
[0038] Furthermore, step S2 in this embodiment specifically includes:
[0039] Step S21: Immerse the aluminum alloy substrate with the anodic oxide film in a low-viscosity conductive primer for 1-3 minutes to allow the conductive primer to penetrate into the nanoporous honeycomb structure of the anodic oxide film. The working viscosity of the conductive primer is 8-12s. The low viscosity of the primer has low flow resistance, which can fully wet the surface of the oxide film and penetrate into the pores of the nanoporous honeycomb structure. The 1-3 minute immersion time provides sufficient time for the primer to penetrate into the pores, creating conditions for the formation of high-density nanomechanical anchoring sites. If the viscosity is too high or the immersion time is insufficient, the primer will not be able to effectively penetrate into the micropores, and the anchoring effect will decrease. If the viscosity is too low or the immersion time is too long, the surface paint film will be too thin, which is not conducive to subsequent film formation.
[0040] Step S22: The conductive primer is cured. The primer that penetrates into the pores is cured and formed into a mechanical anchor structure in the pores, realizing physical interlocking with the anodized film. At the same time, a complete and continuous conductive primer layer is formed on the surface of the oxide film. This primer layer serves as an intermediate transition layer, which can buffer the difference in thermal properties between the bottom aluminum alloy-anodized film and the upper graphene conductive heating layer, alleviate interlayer thermal stress under hot and cold cycling conditions, and provide a good wetting base for subsequent graphene coatings, ensuring uniform spreading of the upper coating.
[0041] In this embodiment, the conductive primer formulation includes 100 parts epoxy-modified acrylic resin, 10 parts conductive carbon black, 4 parts graphene microplates, 2.5 parts KH-550 coupling agent, 3 parts nano alumina, 6 parts reactive diluent AGE, 1.5 parts dispersant BYK-163, 0.5 parts leveling agent BYK-333, an appropriate amount of butyl acetate / xylene mixed solvent, and isocyanate curing agent N75 mixed at a ratio of NCO / OH = 1.1.
[0042] Step S3: Coat at least one layer of graphene coating on the surface of the conductive primer layer, and obtain at least one conductive heating layer after gradient curing; Coating the conductive primer layer with graphene coating ensures that the graphene coating can be evenly spread by relying on the good interface conditions of the underlying conductive primer; The gradient curing method can avoid defects such as rapid boiling and bubbling of solvent and stress concentration of paint film caused by excessively rapid heating of the coating, reduce the risk of pinholes and cracking of the coating, ensure the integrity of film formation, and at the same time facilitate the uniform distribution of graphene filler inside the coating, stabilize and control the sheet resistance of the conductive heating layer, improve the uniformity of heating, reduce local overheating and heating dead zones, and ensure the stable and reliable electrothermal performance of the blade.
[0043] Furthermore, step S3 in this embodiment specifically includes:
[0044] Step S31: Apply graphene coating within 25-35 minutes after the conductive primer layer has dried and cured, so that the conductive primer is kept in a state of surface dryness but not fully cross-linked. Active groups that can participate in the reaction are still retained inside the primer, thereby achieving the wet-on-wet process effect. In the subsequent curing stage, it can chemically react with the components of the graphene coating system to form chemical bonds at the interface between the two layers, further enhancing the interlayer bonding force between the conductive primer layer and the conductive heating layer, and avoiding the problem of interlayer peeling that easily occurs when the two coating layers rely solely on physical adhesion.
[0045] Step S32: After coating with graphene coating, dry it sequentially at 60℃ for 5 min, at 80℃ for 10 min, and at 120℃ for 15 min to obtain a conductive heating layer after gradient curing. In this process, the low temperature stage allows the solvent inside the coating to evaporate slowly and steadily, avoiding defects such as blistering and pinholes caused by rapid boiling of the solvent. The medium temperature stage continuously completes solvent removal and coating pre-crosslinking. The high temperature stage completes full curing and crosslinking of the coating, slows down the concentration of paint film shrinkage stress, reduces the risk of coating cracking, and is conducive to the uniform distribution of graphene filler in the coating. It also stabilizes and controls the sheet resistance of the conductive heating layer, improves the overall heating uniformity, and reduces the probability of local overheating and heating dead zones.
[0046] Step S33: Repeat step S32 until the target number of conductive heating layers is obtained. By repeatedly performing the coating gradient curing operation in step S32, the total dry film thickness of the conductive heating layer can be flexibly adjusted to compensate for the limitation brought by the upper limit of the single film thickness. This makes it easier to obtain a conductive heating layer that meets the target sheet resistance and conductivity requirements. Multi-layer stacking can also reduce the pinhole and micro-defect penetration problems caused by single-layer coating, improve the overall continuity and integrity of the conductive heating layer, and ensure the reliability of the blade's electrothermal operation.
[0047] In this embodiment, the graphene coating preparation process is as follows: PVP dispersant is dissolved in deionized water, rGO graphene powder is added, and the mixture is dispersed at high speed for 1500 rpm × 15 min, then ball-milled at 300 rpm for 2 h in a planetary ball mill. Nano-silver wire dispersion, aqueous polyurethane emulsion, and aziridine crosslinking agent XAMA-7 are added sequentially, and the mixture is stirred at low speed. After degassing under -0.08 MPa vacuum for 10 min, the mixture is filtered through a 100-mesh screen to obtain a final graphene coating with a solid content of approximately 28%. The sheet resistance of the conductive heating layer is approximately 80 Ω / sq, and the uniformity deviation is ≤ ±15%, as measured by a four-probe sheet resistance meter.
[0048] The graphene coating is applied using slot coating or precision roller coating, which enables uniform and stable thin-layer coating, effectively controlling the wet film thickness, reducing film thickness fluctuations, and avoiding problems such as paint splatter and uneven film thickness caused by spraying. This facilitates the formation of a conductive heating layer with uniform sheet resistance, ensuring uniform heating on the blade surface. In this embodiment, slot coating is used to coat the graphene coating onto the workpiece surface after step S3. The coating gap is 150 μm, the coating speed is 2 m / min, and a single coating achieves the target wet film thickness of approximately 170 μm.
[0049] The preparation method of the graphene coating includes: dissolving a dispersant in deionized water, adding graphene powder, and then performing high-speed dispersion and planetary ball milling dispersion in sequence, which can reduce the agglomeration and stacking of graphene and ensure that graphene is uniformly dispersed in the system.
[0050] Then, a nano-silver wire dispersion, an aqueous polyurethane emulsion, and a crosslinking agent are added sequentially. After vacuum degassing and filtration, a target graphene coating with a construction solids content of 25-30% is obtained. Among them, the nano-silver wires can construct auxiliary conductive pathways and improve the conductivity of the coating. The aqueous polyurethane emulsion serves as a binder matrix to provide the coating with film-forming ability and mechanical toughness. The crosslinking agent is used to increase the crosslinking density of the coating and enhance its wear resistance and weather resistance. Vacuum degassing can eliminate air bubbles inside the coating and avoid pinholes and pore defects after film formation. The filtration operation removes residual large particle impurities and prevents scratches and particle protrusion defects during the coating process. By controlling the construction solids content of the coating at 25-30%, it is possible to ensure that the ideal wet film thickness can be achieved in a single coating, while avoiding the problems of poor coating fluidity and poor leveling caused by excessive solids content, or the need for repeated coatings due to excessive solids content. Finally, a graphene coating with stable performance and suitable for slot coating or precision roller coating is obtained.
[0051] In this embodiment, before step S4, a protective topcoat is sprayed onto the electrode area of the conductive heating layer for masking. After high-temperature baking and curing, the cured protective topcoat is removed to expose the electrode area of the conductive heating layer. This allows a complete protective topcoat layer to be formed in the remaining non-electrode areas, protecting the underlying graphene conductive heating layer, blocking moisture, salt spray, and wind and sand abrasion, and improving the overall weather resistance and corrosion resistance of the coating. The electrode positions are precisely exposed by masking and then removing the topcoat after curing, avoiding the protective topcoat covering the electrode connection area and causing insulation blockage. This ensures good electrical contact between the subsequent metal electrode and the graphene conductive heating layer, reduces interface contact resistance, and ensures a smooth and reliable conductive path. At the same time, this masking process ensures neat masking boundaries and reduces the risk of poor contact caused by topcoat overflow contaminating the electrode area.
[0052] In this embodiment, the protective topcoat formulation includes 100 parts PVDF fluorocarbon resin, 6 parts nano-silica, 2.5 parts nano-zinc oxide, 4 parts PTFE micro powder, 1.5 parts dispersant, 0.5 parts leveling agent, BL-3175 blocked isocyanate curing agent according to the specified ratio, and an appropriate amount of NMP / butyl acetate mixed solvent (1 / 3 volume ratio). Two coats of the protective topcoat are applied using an HVLP spray gun, resulting in a dry film thickness of approximately 40 μm. The coating is then baked and cured at 160°C for 20 minutes in an oven. After cooling to below 60°C, the masking tape is removed, and the masking edges are checked for neatness. If a small amount of topcoat has seeped in, it is lightly sanded away with 1000-grit sandpaper.
[0053] After coating the electrode area with silver conductive adhesive, metal electrodes are attached and installed. After hot-pressing and curing, the target electrothermal antifreeze rain-sand separator blade is obtained. The silver conductive adhesive possesses excellent conductivity and interface filling capabilities, fully adhering to the microscopic surface of the graphene conductive heating layer, filling micro-gaps at the interface, and effectively reducing the contact resistance between the electrode and the heating layer, avoiding incomplete connections or poor contact. Combined with the hot-pressing curing process, the silver conductive adhesive can fully cross-link and cure, tightly adhering to the coating and metal electrode, improving the bonding strength and structural stability of the electrode structure. This eliminates the problems of electrode detachment and contact failure under long-term hot-cold cycling and wind-blown sand vibration conditions. Simultaneously, a stable and continuous conductive path is constructed, ensuring that the external power supply can uniformly and continuously power the graphene conductive heating layer, enabling the blade to achieve uniform Joule heating and stably achieve antifreeze and de-icing effects. Finally, a complete electrothermal antifreeze rain-sand separator blade with a complete structure, reliable electrical performance, and weather resistance is produced.
[0054] Step S4: A metal electrode is led out from the conductive heating layer. By leading the metal electrode out from the conductive heating layer, a reliable electrical connection is established between the external power supply and the graphene conductive heating layer, ensuring that the current can be smoothly passed into the conductive heating layer. Joule heating is used to achieve active heating, antifreezing, and de-icing of the blades, completing the integration of electrothermal functions and ultimately obtaining a finished electrothermal antifreeze rain-sand separator blade that meets the usage requirements. In this embodiment, the metal electrode is connected to the conductive heating layer after being hot-pressed and cured in a 150℃ oven for 30 minutes.
[0055] Example 2: See Figure 2 As shown, this embodiment provides an electrothermal antifreeze rain and sand separator blade, which is processed using the electrothermal antifreeze rain and sand separator blade manufacturing method described in Embodiment 1. It includes: an aluminum alloy substrate 100; an anodized film 200, the anodized film 200 covering the surface of the aluminum alloy substrate 100, on which a nanoporous honeycomb structure is arranged; at least one conductive primer layer 300, the conductive primer layer 300 covering the surface of the anodized film 200, and at least a portion of the conductive primer layer 300 penetrating into the channels of the nanoporous honeycomb structure to form a nanomechanical anchoring structure; and a conductive heating layer 400, the conductive heating layer 400 covering the surface of the conductive primer layer 300, and its end having a metal electrode that can be connected to an external power source.
[0056] Among them, the aluminum alloy substrate 100 serves as the main body of the blade and bears the main structural load. The aluminum alloy material is easy to process and form into profiles, is lightweight and has good mechanical strength, which can meet the structural requirements of the rain and sand separator blade to withstand long-term airflow scouring and sandstorm impact, while providing a reliable adhesion substrate for various functional coatings on the surface.
[0057] The anodized film 200 is coated on the surface of the aluminum alloy substrate 100. It has high insulation properties and can form an insulating barrier between the conductive primer layer 300 and the aluminum alloy substrate 100, preventing leakage of current to the aluminum alloy substrate 100 when the conductive heating layer 400 is energized, thus improving the safety of product use. At the same time, the anodized film 200 has an open nanoporous honeycomb structure, which provides micropore space for the conductive primer and serves as the carrier basis for constructing the nanomechanical anchoring structure.
[0058] In this embodiment, the anodic oxide film 200 has a thickness of 4 μm and is not sealed, thus preserving a complete nanoporous honeycomb structure with a pore size of approximately 20 nm, a pore depth of approximately 4 μm, and a pore density of approximately 10. 10 The number of pores per cm² is approximately 80 nm. The oxide film has a hardness of approximately 350 HV and a resistivity of approximately 10¹² Ω·cm.
[0059] In different embodiments, the thickness of the anodic oxide film 200 can be configured to be 3~5μm according to actual usage requirements. This can form a complete and continuous insulating barrier layer, ensuring sufficient insulation resistance between the aluminum alloy substrate 100 and the conductive coating above, meeting electrical safety requirements. At the same time, it can generate a well-developed nanoporous honeycomb structure, providing sufficient pore space for the conductive primer to penetrate and build nanomechanical anchoring sites. The film thickness is not too small, which would result in insufficient insulation capacity and a limited number of micropores, thus reducing the anchoring effect. It can also avoid the increase in internal stress and brittleness caused by an excessively thick film layer, preventing microcracks from appearing in the oxide film 200 under alternating hot and cold conditions, and ensuring the stability and reliability of the interface of the entire composite coating system.
[0060] The conductive primer layer 300 is coated on the surface of the anodic oxide film 200 and partially penetrates into the nanoporous honeycomb structure of the anodic oxide film 200. After curing, it forms a nanomechanical anchoring structure in the micropores. By relying on physical interlocking, it greatly improves the interfacial bonding force between the conductive primer layer 300 and the anodic oxide film 200, reducing the risk of delamination and peeling of the coating under thermal cycling and wind and sand abrasion conditions. The conductive primer layer 300 also serves as an intermediate transition layer to alleviate the difference in thermal expansion performance between the inorganic anodic oxide film 200 and the organic conductive heating layer 400, reduce interlayer thermal stress, and provide a well-wetting coating substrate for the upper conductive heating layer 400, ensuring that the conductive heating layer 400 forms a uniform film.
[0061] The conductive primer layer 300 includes components that make its sheet resistance ≤ 10. 4 The conductive carbon black and graphene microflakes with an Ω / sq density have a dry film thickness of 10~20μm, preferably 15μm in this embodiment, and the conductive primer layer 300 penetrates ≥1.5μm into the nanoporous honeycomb structure channels. Specifically, the sheet resistance of the conductive primer layer 300 is controlled to ≤10. 4 The Ω / sq value enhances the conductivity of the primer itself, reduces the interfacial contact resistance between the primer and the upper conductive heating layer 400, and facilitates heat conduction. The dry film thickness is limited to 10~20μm. If the dry film thickness is too low, it is difficult to form a complete and continuous intermediate transition film layer, which cannot effectively buffer the interlayer thermal stress. If the dry film thickness is too high, it will increase the overall thermal resistance of the coating, which is not conducive to the transfer of heat to the blade surface. The penetration depth of the conductive primer layer 300 in the nanoporous honeycomb structure channel is limited to ≥1.5μm to ensure that the primer fully penetrates into the channel of the oxide film 200, forming a sufficiently deep mechanical interlocking anchoring structure, avoiding adhesion only on the surface of the pore opening, and preventing interfacial debonding under external force and thermal cycling, effectively ensuring a firm bond between the conductive primer layer 300 and the anodic oxide film 200.
[0062] The conductive heating layer 400 covers the surface of the conductive primer layer 300 and is connected to a metal electrode at its end. After being energized, it generates heat by relying on the Joule heating effect to uniformly heat the entire blade, achieving active antifreeze, de-icing and de-icing, avoiding duct blockage caused by rain and snow icing, without changing the original shape and structure of the blade, and without interfering with the airflow of rain and sand separation, thus taking into account both ventilation and de-icing functions. The metal electrode serves as a conductive connection component between the external power supply and the conductive heating layer 400, ensuring a stable current input to the conductive heating layer 400 and ensuring the stable realization of the heating function.
[0063] The number of graphene conductive heating layers 400 can be configured from 1 to 5 layers according to actual usage requirements, so as to flexibly adjust the overall sheet resistance and heating power of the coating and adapt to the anti-freezing and de-icing requirements under different working conditions. Each of the graphene conductive heating layers 400 includes graphene and a bonding substrate, with a sheet resistance of 30~150Ω / sq and a dry film thickness of 30~60μm. If the thickness is too small, it is not easy to form a continuous conductive path, and local open circuits are likely to occur. If the thickness is too large, the sheet resistance will be too low and the working power will exceed the design range. This parameter range can obtain a uniform and stable conductive network, ensuring uniform heating of the blades, avoiding local overheating or heating dead zones, and enabling the blades to stably achieve Joule heating, meeting the active anti-freezing and de-icing requirements of the rain-sand separator blades. The graphene is reduced graphene oxide or liquid-phase exfoliated graphene with a sheet diameter of 5~20μm and a carbon-oxygen ratio ≥8. The binder is an aqueous polyurethane dispersion, which can reduce graphene sheet defects, ensure the excellent electrical and thermal conductivity of the filler itself, and facilitate the construction of a continuous and stable conductive network. As a binder, the aqueous polyurethane dispersion can give the coating good toughness, adhesion and weather resistance, and alleviate the film stress during the thermal cycling process.
[0064] Furthermore, the graphene conductive heating layer 400 in this embodiment also includes silver nanowires. The silver nanowires can work together with graphene to build a multidimensional composite conductive network, fill the conductive gaps between graphene sheets, reduce the risk of local conductive breaks in the coating, make the conductive path of the coating more continuous and complete, which is conducive to the stable control of the coating sheet resistance and improves the overall heating uniformity. At the same time, the good conductivity of the silver nanowires can reduce the overall resistivity of the coating, which can adapt to a larger heating power under the same working voltage conditions, improve the efficiency of blade de-icing and antifreezing, and also alleviate the problem of increased coating brittleness caused by excessive graphene filler, improve the coating stress performance, improve the stability of the conductive performance of the coating after undergoing alternating hot and cold cycles, and reduce resistance drift during long-term use.
[0065] In this embodiment, the blades of the electrothermal antifreeze rain and sand separator also include a silane coupling agent layer. The silane coupling agent layer is disposed between the anodic oxide film 200 and the conductive primer layer 300. One end of the silane coupling agent can chemically react with the inorganic hydroxyl groups on the inner wall of the pores of the anodic oxide film 200 to form covalent bonds, and the other end can form a compatible bond with the organic components of the conductive primer layer 300, thus building a chemical bonding bridge between the inorganic oxide film 200 and the organic conductive primer layer 300. It works synergistically with the nanomechanical anchoring structure formed by the conductive primer layer 300 penetrating into the pores to achieve a dual effect of chemical bonding and physical anchoring, further strengthening the interlayer interface bonding strength, weakening the interface stress, suppressing micro-debonding at the interface under alternating hot and cold conditions and repeated scouring by wind and sand, reducing the risk of coating peeling and flaking, and improving the surface wettability of the anodic oxide film 200, making it easier for the conductive primer layer 300 to better penetrate into the interior of the nanoporous honeycomb pores, ensuring the full formation of the nanomechanical anchoring structure.
[0066] The blades of the electrothermal antifreeze rain and sand separator also include a protective topcoat layer 500, which is connected to the surface of the conductive heating layer 400. The dry film thickness is 30~50μm, preferably 40μm in this embodiment. This allows for a full-coverage protective barrier to the lower conductive heating layer 400 without affecting the electrical connection of the electrodes or hindering the normal operation of the blades' electrothermal function. The moderate dry film thickness of 30~50μm can balance the integrity of the protection with the overall flexibility of the coating, avoiding the problems of insufficient protection due to excessively thin film and easy cracking and peeling due to excessively thick film.
[0067] At least a portion of the conductive heating layer 400 is exposed outside the protective topcoat layer 500. The protective topcoat layer 500 includes nano-silica and polytetrafluoroethylene (PTFE) micropowder. The nano-silica effectively improves the hardness, wear resistance, salt spray resistance, and aging resistance of the topcoat layer 500, resisting outdoor wind and sand erosion, rainwater erosion, and UV aging damage. The PTFE micropowder imparts excellent low surface energy, hydrophobicity, and self-cleaning properties to the coating, reducing the adhesion and accumulation of rain, snow, dust, and dirt on the blade surface. This reduces the probability of blade icing and sand accumulation from the source. The dual-function fillers work synergistically to significantly improve the overall weather resistance and service stability of the blade, effectively delaying the aging, wear, and resistance drift of the bottom conductive heating layer 400, and significantly extending the service life of the electrothermal antifreeze rain and sand separator blades.
[0068] In this embodiment, the metal electrode includes a silver conductive adhesive layer and a copper busbar. The copper busbar is electrically connected to the exposed conductive heating layer 400 through the silver conductive adhesive layer. The copper busbar has excellent conductivity and mechanical flexibility, serving as a stable conductive carrier to achieve efficient current conduction between the external power supply and the heating layer 400. The silver conductive adhesive layer in the middle can fully fill the microscopic gaps between the copper busbar and the graphene conductive heating layer 400, greatly reducing the interface contact resistance and avoiding problems such as uneven heating and contact arcing caused by gaps at the interface. At the same time, the silver conductive adhesive has good conductivity and adhesion properties, which can firmly adhere and fix the copper busbar to the surface of the conductive heating layer 400. Combined with hot pressing and curing, it forms an integrated connection structure, effectively resisting airflow vibration and alternating thermal stress during equipment operation, preventing electrode loosening, peeling, and contact failure, ensuring long-term stability and uniform conductivity of the conductive path in the electrode area, and ensuring the continuous and reliable electrothermal antifreeze performance of the blade.
[0069] Comparative Example 1: To verify the effect of using a thin anodic oxide film (unsealed) instead of a chemical conversion film to improve coating adhesion, the following comparative experiment was conducted:
[0070] Control sample A: A chromium-free chemical conversion film (zirconium-titanium based, film thickness approximately 0.5 μm) was used to replace the anodic oxide film, and the remaining coating structure and process were the same as in Example 1.
[0071] Control sample B: A conventional anodic oxide film (film thickness 15 μm, hot water sealing treatment) was used, and the remaining coating structure and process were the same as in Example 1.
[0072] The adhesion test results of the three groups of samples are shown in Table 1.
[0073] Table 1. Results of adhesion force comparison test
[0074] Initial state cross-cut adhesion Level 0 Level 1 Level 2 Adhesion after soaking in boiling water for 20 minutes Level 0 Level 2 Level 3 Adhesion after 100 cycles of hot and cold cycling Level 0 Level 1 Level 2 Pull-out adhesion 18.5MPa 8.2MPa 5.6MPa
[0075] The results show that the adhesion of the thin anodic oxide film (unsealed) of this invention is significantly better than that of the chemical conversion film and the sealed conventional anodic oxide film. Control sample B showed the worst adhesion, confirming that the sealing treatment clogs the nanopores and reduces the mechanical anchoring effect. The pull-out test fracture in Example 1 of this invention occurred in the primer resin cohesive layer (18.5 MPa), indicating that the bonding force at the anodic oxide film-primer interface exceeded the cohesive strength of the resin itself, reaching the theoretical maximum value.
[0076] Comparative Example 2: The following accelerated aging test was conducted on the sample of Example 2 in this comparative example:
[0077] (1) QUV ultraviolet aging (UVA-340 lamp tube, 8h UV / 60℃ + 4h condensation / 50℃ cycle): After 2500 hours, the gloss retention rate is 85%, the color difference ΔE=2.1, and there is no powdering or cracking.
[0078] (2) Damp heat aging (47℃, RH96%): After 1500 hours, the adhesion was still grade 0, with no bubbling or peeling.
[0079] (3) Cold and hot cycling (-40℃×2h→+60℃×2h): No cracking or delamination after 200 cycles, and the resistance change rate is 6.5% (≤10%).
[0080] (4) Neutral salt spray (5% NaCl, 35℃): After 1500 hours, the etched area showed a single-sided etch depth of 0.8 mm (≤2 mm) with no blistering.
[0081] The above results demonstrate that the blades of the present invention have excellent weather resistance.
[0082] In summary, the electrothermal antifreeze rain and sand separator blade manufacturing method and separator blade of the present invention first constructs an anodic oxide film with a nanoporous honeycomb structure on the surface of an aluminum alloy substrate, then allows a conductive primer to penetrate into the pores of the oxide film, relying on the nanomechanical anchoring effect to significantly improve the bonding strength between the conductive primer layer and the substrate interface, and then coats the conductive primer layer with graphene coating and forms a conductive heating layer through gradient curing, which can ensure the uniformity of the graphene conductive heating layer film formation and reduce internal defects of the coating. The finished blade can then be obtained by connecting it with a metal electrode.
[0083] The entire preparation process is simple and controllable, facilitating industrial implementation. The blades produced by this method integrate electrothermal functions into the blade body, eliminating the need for additional external heating components such as electric heating cables and heating wires. This process does not alter the original shape and structure of the blades, nor does it interfere with the internal airflow field of the rain-sand separator. While achieving active electrothermal de-icing and preventing blade icing from blocking the air duct, it also ensures the ventilation and rain-sand separation performance of the equipment. The anodic oxide film also acts as an insulating barrier between the substrate and the conductive primer layer, reducing the risk of leakage. The gradient curing process helps improve the sheet resistance uniformity of the graphene coating, making the overall heating of the blades more uniform and reducing local overheating and heating dead zones. The resulting composite coating system has excellent adhesion and can withstand repeated thermal cycles, salt spray erosion, and wind and sand abrasion. Under long-term outdoor conditions, it is not prone to failure phenomena such as peeling, flaking, or excessive resistance drift, effectively extending the service life of the electrothermal antifreeze rain-sand separator blades.
[0084] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for manufacturing blades of an electrothermal antifreeze rain-sand separator, characterized in that: include: Step S1: The pretreated aluminum alloy substrate is used as an anode for anodizing treatment until an anodized film with a nanoporous honeycomb structure is formed on the surface of the aluminum alloy substrate. Step S2: Coat the surface of the anodic oxide film with a conductive primer until the conductive primer penetrates into the nanoporous honeycomb structure of the anodic oxide film, and obtain a conductive primer layer after drying and curing. Step S3: Coat at least one layer of graphene coating on the surface of the conductive primer layer, and obtain at least one conductive heating layer after gradient curing; Step S4: Lead out the metal electrode from the conductive heating layer to obtain the target electrothermal antifreeze rain and sand separator blade.
2. The method for manufacturing blades of an electrothermal antifreeze rain-sand separator according to claim 1, characterized in that: Step S1 specifically includes: Step S11: Perform pretreatment on the aluminum alloy substrate, the pretreatment including alkaline degreasing, water washing and acid pickling activation treatment sequentially performed on the surface of the aluminum alloy substrate; Step S12: The pretreated aluminum alloy substrate is placed in a sulfuric acid electrolyte for anodizing treatment, with the current density controlled at 1.0~1.2 A / dm³. 2 The electrolyte temperature is 18~22℃, the oxidation time is 8~15min, until an anodic oxide film with a thickness of 3~5μm is formed on the surface of the aluminum alloy substrate; Step S13: Wash the anodic oxide film with water and dry it to obtain an anodic oxide film with a nanoporous honeycomb structure.
3. The method for manufacturing blades of an electrothermal antifreeze rain-sand separator according to claim 2, characterized in that: In step S12, the concentration of the sulfuric acid electrolyte is 160~180g / L, and the voltage for anodizing starts at 8V and gradually increases to 12~15V as the film thickness increases. In step S13, after anodizing, the film is washed with deionized water with a conductivity ≤50μS / cm, dried, and then proceeds to step S2 within 4 hours to obtain an anodized film with a nanoporous honeycomb structure.
4. The method for manufacturing blades of an electrothermal antifreeze rain-sand separator according to claim 1, characterized in that: Before proceeding to step S2, the anodic oxide film with the nanoporous honeycomb structure needs to be pretreated with silane. The silane pretreatment process includes immersing the aluminum alloy substrate with the anodic oxide film in an ethanol / water solution with a mass concentration of 2% γ-aminopropyltriethoxysilane, soaking it at 60°C for 10 minutes, draining it, and then drying it with hot air at 80°C.
5. The method for manufacturing blades of an electrothermal antifreeze rain-sand separator according to claim 1, characterized in that: Step S2 specifically includes: Step S21: Immerse the aluminum alloy substrate with the anodic oxide film in a low-viscosity conductive primer for 1-3 minutes to allow the conductive primer to penetrate into the nanoporous honeycomb structure of the anodic oxide film, wherein the application viscosity of the conductive primer is 8-12s. Step S22: Curing the conductive primer to obtain the target conductive primer layer.
6. The method for manufacturing blades of an electrothermal antifreeze rain-sand separator according to claim 1, characterized in that: Step S3 specifically includes: Step S31: Apply graphene coating within 25-35 minutes after the conductive primer layer has dried and cured; Step S32: After coating with graphene coating, dry it sequentially at 60°C for 5 min, at 80°C for 10 min, and at 120°C for 15 min to obtain a conductive heating layer after gradient curing. Step S33: Repeat step S32 until the target number of conductive heating layers is obtained; The graphene coating is applied by slot coating or precision roller coating. The preparation method of the graphene coating includes: dissolving a dispersant in deionized water, adding graphene powder and then dispersing it by high-speed dispersion and planetary ball milling, then adding nano-silver wire dispersion, water-based polyurethane emulsion and crosslinking agent, and filtering after vacuum degassing to obtain a target graphene coating with a construction solids content of 25-30%.
7. The method for manufacturing blades of an electrothermal antifreeze rain-sand separator according to claim 1, characterized in that: Before step S4, a protective topcoat is sprayed onto the electrode area of the conductive heating layer to mask it. After high-temperature baking and curing, the cured protective topcoat is removed to expose the electrode area of the conductive heating layer. After coating the electrode area with silver conductive adhesive, the metal electrode is attached and installed. After hot pressing and curing, the target electrothermal antifreeze rain and sand separator blade is obtained.
8. An electrically heated antifreeze rain-sand separator blade, characterized in that: The blades of the electrothermal antifreeze rain-sand separator are manufactured using the method described in any one of claims 1 to 7, and include: Aluminum alloy substrate; An anodized film, wherein the anodized film covers the surface of the aluminum alloy substrate and has a nanoporous honeycomb structure arranged thereon; At least one conductive primer layer is provided, which coats the surface of the anodic oxide film and at least a portion of the conductive primer layer penetrates into the channels of the nanoporous honeycomb structure to form a nanomechanical anchoring structure. A conductive heating layer is provided, which covers the surface of the conductive primer layer and has metal electrodes at its ends that can be connected to an external power source.
9. The blades of the electrothermal antifreeze rain-sand separator according to claim 8, characterized in that: The thickness of the anodic oxide film is 3~5μm; The conductive primer layer includes components that have a sheet resistance ≤10. 4 The conductive carbon black and graphene microplates with an Ω / sq dry film thickness of 10~20μm, and the conductive primer layer has a penetration depth ≥1.5μm in the nanoporous honeycomb structure channels; The number of graphene conductive heating layers is 1 to 5, and each of the graphene conductive heating layers includes graphene and a bonding matrix, with a sheet resistance of 30 to 150 Ω / sq and a dry film thickness of 30 to 60 μm. The graphene is reduced graphene oxide or liquid-phase exfoliated graphene, with a sheet diameter of 5 to 20 μm and a carbon-to-oxygen ratio ≥ 8. The bonding matrix is an aqueous polyurethane dispersion. The graphene conductive heating layer also includes silver nanowires.
10. The blades of the electrothermal antifreeze rain-sand separator according to claim 8, characterized in that: The blades of the electrothermal antifreeze rain and sand separator also include a silane coupling agent layer, which is disposed between the anodic oxide film and the conductive primer layer; The blades of the electrothermal antifreeze rain and sand separator also include a protective topcoat layer, which is connected to the surface of the conductive heating layer. The dry film thickness of the protective topcoat layer is 30~50μm. At least part of the conductive heating layer is exposed outside the protective topcoat layer. The protective topcoat layer includes nano-silica and polytetrafluoroethylene micro powder. The metal electrode includes a silver conductive adhesive layer and a copper busbar, the copper busbar being electrically connected to the exposed conductive heating layer through the silver conductive adhesive layer.